1975
DOI: 10.1136/gut.16.11.876
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone for chronic active liver disease: dose titration, standard dose, and combination with azathioprine compared.

Abstract: SUMMARY Among 120 consecutive patients with chronic active liver disease (CALD) randomized to different treatments, those receiving maintenance doses of prednisone 20 mg daily (Pred), prednisone in doses given on alternate days and titrated to secure resolution of clinical and biochemical abnormalities (Pred-Titrad), or a combination of prednisone 10 mg and azathioprine 50 mg daily (Comb) survived and underwent resolution of clinical and biochemical features of disease more often than a control group receiving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
195
1
4

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(202 citation statements)
references
References 17 publications
2
195
1
4
Order By: Relevance
“…Each schedule had been shown previously to be equally effective in treating autoimmune hepatitis. 28 Twenty-six patients (13%) either did not satisfy criteria for treatment (17 patients) or received investigational therapies (9 patients). These 26 patients were not included in the analyses of outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Each schedule had been shown previously to be equally effective in treating autoimmune hepatitis. 28 Twenty-six patients (13%) either did not satisfy criteria for treatment (17 patients) or received investigational therapies (9 patients). These 26 patients were not included in the analyses of outcome.…”
Section: Methodsmentioning
confidence: 99%
“…It was previously shown that the 2 treatment regimens were of comparable efficacy. 43 All patients satisfied pretreatment scoring criteria for a definite diagnosis of autoimmune hepatitis (mean score, 18 Ϯ 0.1 points; median, 18 points, range, 16-24 points) and had smooth muscle antibodies (65 patients), antinuclear antibodies (56 patients), or both (93 patients) at accession. One hundred ninety-six patients tested for antibodies to liver kidney microsome type 1 (anti-LKM1) were negative for this marker.…”
Section: Methodsmentioning
confidence: 99%
“…Intolerable cosmetic effects, osteopenia with vertebral compression, emotional instability, brittle diabetes, and/or labile hypertension constituted drug intolerance. 25,26 Clinical and laboratory improvement insufficient to justify drug withdrawal constituted an incomplete response. Under such circumstances, therapy was continued, and dosages of medication were adjusted to the lowest levels needed to maintain serum AST levels below 5-fold normal.…”
Section: Methodsmentioning
confidence: 99%
“…Fifty-eight patients (69%) were treated with prednisone in combination with azathioprine, and 26 patients (31%) received a higher dose of prednisone alone. These treatments had been shown previously to be of comparable efficacy, 25 and outcomes were analyzed in all patients regardless of individual regimen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation